Computational micro fluid dynamics using COMSOL multiphysics for sample delivery in sensing domain - Uda, Hashim, Prof. Dr.; Tijjani Adam, Shuwa; Diyana, P. N. A.; Ten, Seng Teik (Institute of Electrical and Electronic Engineers (IEEE), 2013)
link to publisher's homepage at http://ieeexplore.ieee.org/